Madrasah Head Policy in Managing Extra-Curricular Organizations at Madrasah Tsanawiyah Negeri 10 Indramayu - Fiqih Amrullah; Ani Ramayanti; Dede Ahmad Ramdani; Qiqi Yuliati Zaqiah; Bambang Qomaruzzaman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The Head of Madrasah is able to carry out his mandate well, carry out his function as supervision in the school also optimally, and when making decisions for the benefit of the school is done wisely without any personal interest, and is able to carry out the Vision, Mission of a superior Madrasah for the implementation of effective Madrasah learning. Positive Response is something that must be owned by the Head of Madrasah in the implementation of this School Extracurricular Activity. The Head of Madrasah is the Top Leader who has all policies related to Madrasah activities. The progress or failure of an extracurricular organization depends on the attitude and responsiveness of the head of the Madrasah. Policy is the result of decisions taken wisely and wisely for the benefit of a person or group of people in order to achieve the expected goals by moving forward in the future. This research is a case study that came to the research location by directly collecting the object of research at the research location. The type of research is analytical descriptive with a qualitative approach, aiming to understand the phenomena that occur in food concretely to obtain scientific knowledge that can be accounted for. The policy of the head of the Madrasah will oversee the working mechanism of the madrasah which has a considerable role in improving the quality of the madrasah. Policies that can encourage the improvement of madrasah quality will greatly affect the development of madrasah.